Economically Motivated Adulteration of Lemon Juice: Cavity Ring Down Spectroscopy in Comparison with Isotope Ratio Mass Spectrometry: Round-Robin Study. (3rd December 2019) - Mantha, Madhavi; Kubachka, Kevin M; Urban, John R; Dasenbrock, Catherine O; Chernyshev, Anatoly; Mark, William A; France, Christine; Chartrand, Michelle; Hache, Jonathan; Decoeur, Sylvain; Qi, Haiping
Abstract: Background: Economically motivated adulteration (EMA) of foods has become an increasing concern in recent years, with lemon juice as a popular target. Objective and Method: In this work, an optimized preparation procedure for the isolation of citric acid from lemon juice was validated using elemental analyzer-isotope ratio MS (EA-IRMS) to detect adulteration with exogenous citric acid. Additionally, 69 imported lemon juice samples were evaluated using combustion module-cavity ring down spectrometry (CM-CRDS) and compared with the well-established EA-IRMS. Equivalency of CM-CRDS to EA-IRMS was further demonstrated by conducting a round-robin study involving eight laboratories throughout the United States, Canada, and New Zealand. Results: Overall, the results obtained for CM-CRDS were statistically indistinguishable from the results obtained using EA-IRMS for EMA lemon juice analysis. Conclusions: Therefore, CM-CRDS is a viable option for this application. Highlights: The CM-CRDS instrumentation is easy to operate, robust, and provides δ 13 C values comparable to EA-IRMS for citrate analysis. Through a multi-laboratory exercise, CM-CRDS was shown to be an alternative to EA-IRMS in the detection of economic adulteration of lemon juice.